2000
DOI: 10.1016/s0022-5347(05)67908-6
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Epididymo-Orchitis in Patients With Behçet’s Disease

Abstract: Epididymo-orchitis in patients with Behçet's disease is not as infrequent as believed. It was not the first manifestation of the disease but developed during followup. In any patient with epididymo-orchitis Behçet's disease should be considered, particularly in regions with a high prevalence of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…The anti‐arrhythmic drug amiodarone can rarely provoke a reversible sterile epididymitis [47]. Other rare noninfective causes include vasculitis; epididymitis has been reported in patients with polyarteritis nodosa, Behçet's disease and Henoch‐Schonlein purpura [48–50]. A proportion of cases of acute epididymitis remains idiopathic.…”
Section: Other Causesmentioning
confidence: 99%
“…The anti‐arrhythmic drug amiodarone can rarely provoke a reversible sterile epididymitis [47]. Other rare noninfective causes include vasculitis; epididymitis has been reported in patients with polyarteritis nodosa, Behçet's disease and Henoch‐Schonlein purpura [48–50]. A proportion of cases of acute epididymitis remains idiopathic.…”
Section: Other Causesmentioning
confidence: 99%
“…The incidence of epididymo-orchitis was 31% in Iraqi but only 6% in Turkish patients. 4 Zouboulis et al 5 reported prostatitis and epididymo-orchitis with BD in 22% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Infection has also been implicated; however, urinary cultures have consistently been negative in case series, and inflammation subsides with administration of anti-inflammatory drugs. 4 , 6 Clinical presentation in different case series and reports was mainly as testicular pain, with testicular mass being less common. 7 , 8 , 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes of the testes, especially viral orchitis, trauma or side-effects of medication, such as amiodaron and some vasculopathies, need to be excluded. 6,7 In cases of recurrent EO, infectious causes such as brucella and tuberculosis must be considered. 8,9 In this case, presumably the acute and recurrent EO was caused by systemic infection associated with neutropenia.…”
Section: Discussionmentioning
confidence: 99%